An Overview of the Heterogeneity of Major Depressive Disorder: Current Knowledge and Future Prospective - Athira, Kaipuzha V.; Bandopadhyay, Sikta; Samudrala, Pavan Kumar; Naidu, V.G.M.; Lahkar, Mangala; Chakravarty, Sumana (Current Neuropharmacology, 2020)
Major depressive disorder (MDD) is estimated to impose maximum debilitating effects on the society by 2030, with its critical effects on health, functioning, quality of life and concomitant high levels of morbidity and mortality. Yet, the disease is inadequately understood, diagnosed and treated. Moreover, with the recent drastic rise in the pace of life, stress has materialized as one of the most potent environmental factors for depression. In this scenario, it is important to understand the modern pathogenetic hypotheses and mechanisms, and possibly try to shift from the traditional approaches in depression therapy. These include the elaboration of pathophysiological changes in heterogeneous systems such as genetic, epigenetic, serotonergic, noradrenergic, gammaaminobutyric acid, glutamatergic and endocannabinoid systems, neurotrophic factors, HPA axis, immune system as well as cellular stress mechanisms. These components interact with each other in a complex matrix and further elucidation of their mechanism and cascade pathways are needed. This might aid in the identification of MDD subtypes as well as the development of sophisticated biomarkers. Further, characterization might also aid in developing multitargeted therapies that hold much promise as compared to the conventional monoamine based treatment. New candidate pharmacons, refined psychotherapeutic modalities, advanced neuro-surgical and imaging techniques as well as the implementation of pharmacokinetic, pharmacogenetic prescribing guidelines constitute the emerging expanses of MDD treatment.
Keywords: MDD